Improving microalgae biofuel production: an engineering management approach - Mathew, Domoyi Castro (Cranfield University, 2014)
The use of microalgae culture to convert CO2 from power plant flue gases into biomass that are readily converted into biofuels offers a new frame of opportunities to enhance, compliment or replace fossil-fuel-use. Apart from being renewable, microalgae also have the capacity to utilise materials from a variety of wastewater and the ability to yield both liquid and gaseous biofuels. However, the processes of cultivation, incorporation of a production system for power plant waste flue gas use, algae harvesting, and oil extraction from the biomass have many challenges. Using SimaPro software, Life cycle Assessment (LCA) of the challenges limiting the microalgae (Chlorella vulgaris) biofuel production process was performed to study algae-based pathway for producing biofuels. Attention was paid to material use, energy consumed and the environmental burdens associated with the production processes. The goal was to determine the weak spots within the production system and identify changes in particular data-set that can lead to and lower material use, energy consumption and lower environmental impacts than the baseline microalgae biofuel production system. The analysis considered a hypothetical transesterification and Anaerobic Digestion (AD) transformation of algae-to- biofuel process. Life cycle Inventory (LCI) characterisation results of the baseline biodiesel (BD) transesterification scenario indicates that heating to get the biomass to 90% DWB accounts for 64% of the total input energy, while electrical energy and fertilizer obligations represents 19% and 16% respectively. Also, Life Cycle Impact Assessment (LCIA) results of the baseline BD production scenario show high proportional contribution of electricity and heat energy obligations for most impact categories considered relative to other resources. This is attributed to the concentration/drying requirement of algae biomass in order to ease downstream processes of lipid extraction and subsequent transesterification of extracted lipids into BD. Thus, four prospective alternative production scenarios were successfully characterised to evaluate the extent of their impact scenarios on the production system with regards to lowering material use, lower energy consumption and lower environmental burdens than the standard algae biofuel production system. A 55.3% reduction in mineral use obligation was evaluated as the most significant impact reduction due to the integration of 100% recycling of production harvest water for the AD production system. Recycling also saw water demand reduced from 3726 kg (freshwater).kgBD- 1 to 591kg (freshwater).kgBD- 1 after accounting for evaporative losses/biomass drying for the BD transesterification production process. Also, the use of wastewater/sea water as alternative growth media for the BD production system, indicated potential savings of: 4.2 MJ (11.8%) in electricity/heat obligation, 10.7% reductions for climate change impact, and 87% offset in mineral use requirement relative to the baseline production system. Likewise, LCIA characterisation comparison results comparing the baseline production scenarios with that of a set-up with co-product economic allocation consideration show very interesting outcomes. Indicating -12 MJ surplus (-33%) reductions for fossil fuels resource use impact category, 52.7% impact reductions for mineral use impact and 56.6% reductions for land use impact categories relative to the baseline BD production process model. These results show the importance of allocation consideration to LCA as a decision support tool. Overall, process improvements that are needed to optimise economic viability also improve the life cycle environmental impacts or sustainability of the production systems. Results obtained have been observed to agree reasonably with Monte Carlo sensitivity analysis, with the production scenario proposing the exploitation of wastewater/sea water to culture algae biomass offering the best result outcome. This study may have implications for additional resources such as production facility and its construction process, feedstock processing logistics and transport infrastructure which are excluded. Future LCA study will require extensive consideration of these additional resources such as: facility size and its construction, better engineering data for water transfer, combined heat and power plant efficiency estimates and the fate of long-term emissions such as organic nitrogen in the AD digestate. Conclusions were drawn and suggestions proffered for further study.
Keywords: CO2; biomass; fossil fuel; Life Cycle Assessment (LCA); Chlorella vulgaris; Anaerobic Digestion (AD); Transesterification; Monte Carlo sensitivity analysis